2021
DOI: 10.3390/cells10030614
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor Regulatory Noncytotoxic NK Cells in Patients with Hepatocellular Carcinoma

Abstract: Previous studies support the role of natural killer (NK) cells in controlling hepatocellular carcinoma (HCC) progression. However, ambiguity remains about the multiplicity and the role of different NK cell subsets, as a pro-oncogenic function has been suggested. We performed phenotypic and functional characterization of NK cells infiltrating HCC, with the corresponding nontumorous tissue and liver from patients undergoing liver resection for colorectal liver metastasis used as controls. We identified a reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…The dual capability of anti-CD6 monoclonal antibody to enhance killing of cancer cells through its effects on both CD8 + T cells and NK cells opens a new avenue for cancer immunotherapy [92]. Tumor infiltrating NK cells co-expressing CD49a and Eomes of 18 with reduced cytotoxic potential, have been reported in HCC and this NK cell subset was implicated to have proangiogenic function [93].…”
Section: Nk Cells-based Immunotherapy Of Hccmentioning
confidence: 99%
“…The dual capability of anti-CD6 monoclonal antibody to enhance killing of cancer cells through its effects on both CD8 + T cells and NK cells opens a new avenue for cancer immunotherapy [92]. Tumor infiltrating NK cells co-expressing CD49a and Eomes of 18 with reduced cytotoxic potential, have been reported in HCC and this NK cell subset was implicated to have proangiogenic function [93].…”
Section: Nk Cells-based Immunotherapy Of Hccmentioning
confidence: 99%
“…The expression of granzyme, perforin and IFN-γ were all reduced, resulting in a reduced ability to lyse target cells in vitro [136]. The analyses of normal and tumor hepatic tissues have revealed a strong decrease of intratumoral NK cells in tumors compared to non-tumoral tissues [133,134,138]. Regarding the distribution of the different NK cell subsets within tumors, Zecca et al [138] have reported an enrichment in CD56 bright NK cells, associated with decreased expression of CXCR6 and Eomes and an increased frequency of T-bet + and CD49a + CD56 bright NK cells.…”
Section: Nk Cells In Hccmentioning
confidence: 99%
“…The analyses of normal and tumor hepatic tissues have revealed a strong decrease of intratumoral NK cells in tumors compared to non-tumoral tissues [133,134,138]. Regarding the distribution of the different NK cell subsets within tumors, Zecca et al [138] have reported an enrichment in CD56 bright NK cells, associated with decreased expression of CXCR6 and Eomes and an increased frequency of T-bet + and CD49a + CD56 bright NK cells. In contrast, Sun et al [139] observed a decreased frequency of CD56 bright cells with a corresponding increase of CD56 dim NK cells compared to peri-tumoral tissues.…”
Section: Nk Cells In Hccmentioning
confidence: 99%
See 2 more Smart Citations